(untitled) (Altre Modernità, 2012)
This essay, which relies mostly on a cultural studies approach, aims to highlight the discursive and semiotic strategies which have defined official tourism promotion in South Africa since the end of apartheid. In particular, hosting the FIFA World Cup, a mega-event which placed the Country at the crossroads of international touristic flows in 2010, was not so much a finishing line, but rather a turning point for the self-refashioning of the country’s image. Shedding stereotyped definitions such as “the country of the big five”, South African Tourism has rebranded itself so as to mirror the new, complex reality and international status achieved by the nation since the advent of freedom. South Africa’s new public imaginary resembles a challenging, richly-textured prism, whose multiple facets concur to articulate a domestic discourse of reconciliation and unity along with the international projection of a powerful national identity, rebranded for the 21st century. By focusing on the promotion of so diverse branches of tourism as wildlife and conservation, township tourism and sport mega-events, this article aims to shed light on South Africa’s extraordinary achievement in nation-branding over the last decade, and on the way this process has been transformed into an effective tool of nation-building and public diplomacy